Relation between Religious Understanding and Women's Life - Desi Erawati (Budapest International Research and Critics University, 2022)
This study examines how religious understanding and women's life are in Kahayan riverside, Central Kalimantan, Indonesia. This study aims to see whether there is a relationship between the religious understanding and women’s social life. The research method used is naturalistic qualitative by taking purposive samples; there are 12 participants consisting of 5 male laborers or private company workers and 5 housewives, added by supporting informants namely Rukun Warga (RW) and one leader of an equally-sub district area namely RT as participants who understand the pattern of life in the community. Data were obtained through observations for two months in May - June 2019. The data analysis was done by collecting daily records every week and then they were evaluated based on needs. This study found out that a religious doctrine that is textually normative is very influential on the mindset among women/mothers so that it is shaped in their social life.